2015
DOI: 10.21608/ejrci.2015.9213
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and It's Relation to Disease Activity in Egyptian Patients with Systemic Lupus Erythematosus

Abstract: Objective: The aim of the present work is to study the effect of Systemic Lupus Erythematosus( SLE) and its activity on the quality of life in SLE patients. Subjects and Methods: In this study, we investigated One Hundred SLE patients as regards disease activity and its impact on the quality of life (QoL). Disease activity was measured by SLE Disease Activity Index (SLEDAI), and quality of life was measured by Short Form-36 health questionnaire (SF-36). Results: Mucocutaneous, hematological and renal manifesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In an Egyptian study conducted at Tanta University Hospital, all domains were found to be lower in SLE patients, and impairment of physical and emotional domains of QoL with disease activity was also observed 29 . Using the Lupus QoL questionnaire to assess QoL, Jolly et al found that HRQoL was adversely affected, and that longer disease duration was associated with lower QoL scores in SLE patients 30 .…”
Section: Discussionmentioning
confidence: 96%
“…In an Egyptian study conducted at Tanta University Hospital, all domains were found to be lower in SLE patients, and impairment of physical and emotional domains of QoL with disease activity was also observed 29 . Using the Lupus QoL questionnaire to assess QoL, Jolly et al found that HRQoL was adversely affected, and that longer disease duration was associated with lower QoL scores in SLE patients 30 .…”
Section: Discussionmentioning
confidence: 96%